Contemplating GATS Article XVIII on Additional Commitments - Bigos, J. Bradley (2012)
The General Agreement on Trade in Services (GATS) Article XVIII on Additional Commitments is among the least understood articles of the GATS, and it has received the least attention among the articles regulating specific commitments. Nonetheless, the terse language of Article XVIII makes clear that it is inextricably linked with Articles XVI and XVII in the regulation of specific commitments on trade in services. This article undertakes to unravel the complexities of Article XVIII, and to illuminate the types of additional commitments Members have scheduled to date. To do so, it reviews documents from the negotiation history, relevant WTO jurisprudence and existing commentary on Article XVIII. It then suggests how Article XVIII might be interpreted under Articles 31 and 32 of the Vienna Convention on the Law of Treaties. Finally, it indicates five categories into which the additional commitments that have been scheduled to date may be organized.